Tradition in a New Costume: (Re)Presenting Masculinity in Japanese Figure Skating - Hrivnacova, Kristyna (My University, 2024)
Focusing on the displays and construction of masculinity in Japanese figure skating, this thesis carries out a thematic analysis of media content connected to three prominent Japanese skaters. Via the lens of West and Zimmerman’s “doing gender” and Connell’s hegemonic masculinity theories, it examines newspaper reporting, advertisements, and costumes of Yuzuru Hanyu, Shoma Uno, and Yuma Kagiyama, and discusses how the resulting themes support this thesis’ argument for figure skating masculinity as a complicit form of masculinity. The research shows that the three figure skaters both display and are primarily characterised by traditional masculine virtues such as perseverance, single-minded devotion, and dependability, with notions such as expression of emotion and openness regarding mental health playing a marginal role. The thesis further argues that the skaters’ masculinity is portrayed and reaffirmed via their adherence to an adjusted version of the life cycle expected of Japanese men. As research on Japanese masculinities has been largely dominated by the salaryman discourse, this study contributes to the existing research on Japanese masculinities and their construction, and, more broadly, to the generally limited discourse on sporting masculinities in individual and “women’s” sports.
Keywords: masculinity, Japan, figure skating, gender displays, gender construction